Menggali Kreativitas Sastra Melalui Pendekatan Teori Sastra Modern: Implikasi bagi Pengajaran Sastra di Era Digital - Septiari, Wahyu Dini; Marmoah, Sri; Nurhasanah, Farida; Wicaksana, Muhlis Fajar (Jurnal Ilmiah Dikdaya, 2023)
Modern literary theory and technology approaches can be applied in literature teaching to increase students' creativity in understanding and enjoying literary works in the digital era. The use of technology can help students to broaden their horizons about literature and enrich their learning experience, but keep in mind that the use of technology also has some disadvantages. In this study, the author discusses the implications of using modern literary theory approaches and technology in literary teaching, as well as strategies that can be used to utilize technology wisely and effectively in the context of literary teaching. Through this approach, it is hoped that students can develop their creativity in understanding and enjoying literary works better in the digital era.